PEMANFAATAN ICT MELALUI IMPLEMENTASI e-LEARNING BERBASIS INTEGRASI KEISLAMAN DALAM PROSES PEMBELAJARAN - Dicki Hartanto (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2018)
Even the application of e-Learning in UIN Sultan Syarif Kasim Riau has began in 2010, but in learning practice, the e-Learning has not been associated with Islamic integration as Indentifier of Islamic university. Therefore, the researcher interested to have a study, entitled "The Usage of ICT Through e-Learning Based On Islamic Integration in Economic Education Learning Process".The study was conducted at the State Islamic University of Sultan Syarif Kasim Riau from April to June 2015. The population was the students followed e-Learning with number of 429 students and the samples taken was about 10% or 50 samples from total population. The technique used in sampling was 'Random Sampling'.From the research findings, it is seen that the implementation of e-Learning based on the Islamic integration in the learning process was 74.4% and included in good category (range: 61% -80%). This showed that the e-learning management based on Islamic integration has achieved good results. From the results of the open questionnaire and interviews, the respondents' opinions of students are summarized as follows: 1) To provide appropriate materials with Islamic integration, 2) To offer more Islamic learning, 3) To add Islamic inspiring stories, 4 ) To perform more attractive images, 5) To announce information about activities in UIN Suska Riau, 6) To add words and video of Islamic motivation, 7) To add verses of Al-Qur’an and hadiths related to learning, 8) To add a message or advice related to Islam, 9) Each material should be attributed to Islamic context.